The implementation and impact of a pilot hydrocele surgery camp for LF-endemic communities in Ethiopia - Andualem Deneke Beyene (Public Library of Science (PLoS), 2021)
Background Ethiopia aims to eliminate lymphatic filariasis by 2020, through a dual approach of mass drug administration to interrupt transmission and morbidity control which includes making hydrocele surgery available in all endemic areas. Locating patients requiring surgery, providing high quality surgeries, and following up patients are all formidable challenges for many resource-challenged or difficult-to-reach communities. To date, hydrocele surgery in Ethiopia has only occurred when a patient has the knowledge, time and resources to travel to regional hospitals. Ethiopia tested the novel approach of using a surgical camp, defined as mobilizing, transporting, providing surgery at a static site, and following up of a large cohort of hydrocele patients within a hospital’s catchment area, to address delays in seeking and receiving care. Methodology and results Health extension workers mobilized 252 patients with scrotal swelling from a list of 385 suspected hydrocele cases from seven endemic districts in the region of Beneshangul-Gumuz. Clinical health workers and surgeons confirmed 119 as eligible for surgery. Of 70 additional patients who self-referred, 56 were eligible for surgery. Over a two-week period at a regional hospital, 175 hydrocele excision surgeries were conducted. After discharge three days after surgery, trained clinical health workers followed up with the patients on Day 5, Day 8, Day 14 and 1st-month benchmarks with a randomized follow-up of a selection of patients conducted at 9–12 months. There were no post-operative complications upon discharge at Day 3 and 22, while minor complications occurred (12.6%) between Day 3 and one month. The 9–12 month follow-up found patients self-reported an improvement in quality of life, health and economic status. Conclusion A hydrocele surgery camp was effective at providing a large number of quality surgeries in a short time. Using peripheral health workers to mobilize and follow up patients helped address delays in seeking and receiving quality care. Mainstreaming patient mobilization and follow-up into a community health system could be effective in other countries. The camp’s results also influenced two regions in Ethiopia to change their policies in order to offer free hydrocele surgery (including patient transport, consultation, surgery, diagnostic tests and necessary medications). Author summary Hydrocele is a type of scrotal swelling caused by lymphatic filariasis and requires surgery to treat, which can be challenging to address in many endemic countries. Locating and referring patients, providing high quality surgical intervention, and creating a patient follow-up mechanism are all formidable aspects in communities that are often resource challenged and difficult to reach. We explored if the use of a surgical camp setting would be an appropriate intervention to adequately treat a large number of hydrocele patients over a short period, decreasing delays in seeking, reaching and receiving quality surgery for hydrocele. We analyzed each step required to hold the camp including some novel innovations surrounding patient mobilization, referral, and post-surgical quality assurance. The camp was effective at providing a large number of quality surgeries in a short time, with patients self-reporting improvements in quality of life, economic and health status after surgery. The findings from the study may prove useful for countries seeking to implement similar interventions.